2007
DOI: 10.1371/journal.pone.0001271
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Neurotoxin Complex Genes in Clostridium botulinum A1-A4 and B1 Strains: BoNT/A3, /Ba4 and /B1 Clusters Are Located within Plasmids

Abstract: Background Clostridium botulinum and related clostridial species express extremely potent neurotoxins known as botulinum neurotoxins (BoNTs) that cause long-lasting, potentially fatal intoxications in humans and other mammals. The amino acid variation within the BoNT is used to categorize the species into seven immunologically distinct BoNT serotypes (A–G) which are further divided into subtypes. The BoNTs are located within two generally conserved gene arrangements known as botulinum progenitor complexes whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
142
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 59 publications
11
142
0
1
Order By: Relevance
“…BOTULINUM GROUP I GENOTYPING BY 15-LOCUS VNTR 4253 (2,10,14,23,25,26, and 35 RU) were observed for cbms04; four new alleles (7,8,13, and 15 RU) were observed for cbms05; three new alleles (3, 3.5, and 5 RU) were observed for cbms07; one new allele (2 RU) was observed for cbms11; and four new alleles (3, 10, 11, and 12 RU) were observed for cbms14.…”
Section: Vol 49 2011mentioning
confidence: 98%
See 2 more Smart Citations
“…BOTULINUM GROUP I GENOTYPING BY 15-LOCUS VNTR 4253 (2,10,14,23,25,26, and 35 RU) were observed for cbms04; four new alleles (7,8,13, and 15 RU) were observed for cbms05; three new alleles (3, 3.5, and 5 RU) were observed for cbms07; one new allele (2 RU) was observed for cbms11; and four new alleles (3, 10, 11, and 12 RU) were observed for cbms14.…”
Section: Vol 49 2011mentioning
confidence: 98%
“…The clustering of populations using these genotyping methods is only partially congruent with BoNT gene lineage, suggesting that BoNT genes have evolved separately from the bacterial chromosome through horizontal genetic transfer events (2,4,8,10,11). This hypothesis is supported by the discovery, in some C. botulinum strains, of transposable insertion sequences (IS) close to the BoNT genes and of BoNT gene sequences in plasmids (8,24,25,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed-field gel electrophoresis (PFGE) and Southern analysis of strain H04402 065, performed according to the method of Franciosa et al (6), showed that the neurotoxin gene cluster was chromosomally located, as with type A1 neurotoxin genes (10,12), while some type A2 and all types A3 and A4 are plasmid borne (6,12). DNA sequencing of this region revealed a truncated, nonfunctional type B3 gene (7) in the 3Ј flank.…”
mentioning
confidence: 99%
“…This toxin is encoded by the bont gene as part of a cluster that includes nontoxic accessory genes (10). Two main gene clusters are known: the hemagglutinincontaining (haϩ) cluster in toxin serotypes A1, B, C, D, and G and the orfX cluster in toxin serotypes A, E, and F (7,10). In addition, some Clostridium botulinum type A strains (e.g., NCTC2916) contain a silent type B gene in their chromosome, designated A(B).…”
mentioning
confidence: 99%